KEDUDUKAN HUKUM PELAKU USAHA ASING DALAM PRINSIP EXTRATERRITORIALITY JURISDICTION PADA PERSAINGAN USAHA DI INDONESIA: Legal Position Of Foreign Business Actors In The Principle Of Extraterritoriality Jurisdiction In Business Competition In Indonesia - Muhammad Indra Kusumayudha; Simona Bustani (Faculty of Law, Trisakti University, 2023)
The presence of Law Number 5 Year 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition is a real effort for the state to reform the law in the field of economics and business competition law. Against the condition of Indonesia in the vortex of economic globalization that intersects with foreign business actors, there are legal issues that arise are related to the legal position of foreign business actors within the framework of the principle of extraterritoriality jurisdiction and how to anticipate the negative impact of anti-competitive actions committed by foreign business actors based on the principle of extraterritoriality to realize legal certainty. The method used in this research is normative and analytical descriptive research, using secondary data and analyzed qualitatively. The result of the research is the need for improvement and reformulation of the legal position of foreign business actors in the context of extraterritorial jurisdiction in modern competition law. Renewal of business competition law is a necessity considering the needs and dynamics of business competition law that is growing rapidly in the era of global trade. KPPU's institutional strengthening must be carried out continuously and policy innovations must be implemented continuously to adjust to the current needs of competition law. Keywords: Competition Law, Extraterritoriality, Foreign Business Actors, Jurisdiction, KPPU.